Comparative genomics uncovers organellar genome structural divergence in Caryophyllales and reveals widespread non-coding transcription in Bougainvillea glabra organellar - Shuo Zhang; Shengxin Chang; Xinge Lin; Shisong Xu; Qingyun Leng; Haiyan Li; Hernán Ariel López; Junmei Yin; Zhiqiang Wu; Junhai Niu (BMC Genomics)
Abstract Plant organellar genomes play a crucial role in metabolism and adaptation. In this study, the organellar genomes and transcriptome of Bougainvillea glabra (Nyctaginaceae) were sequenced and assembled using PacBio sequencing and strand-specific RNA sequencing, respectively. Structural and evolutionary comparisons of the plastidial and mitochondrial genomes (plastome and mitogenome) were conducted among Bougainvillea and five other taxa within Caryophyllales to elucidate the similarities and divergences between these two organellar genomes at a detailed level. The plastome of B. glabra was assembled into a 154.7 kb circular molecule with a typical quadripartite structure, while the mitogenome was assembled into three stable circular molecules measuring 160.7 kb, 97.6 kb, and 64.3 kb, respectively. Reconstruction of the organellar transcripts revealed extensive transcriptional activity in the non-coding regions of the organellar genomes. However, the transcriptional activity and editing proportions of novel transcripts identified in these regions were significantly lower compared to those of conserved organellar transcripts. A tenfold difference in the number of RNA editing sites was observed between plastidial and mitochondrial transcripts (43 vs. 453), with the majority (70%) of these sites located at nonsilent sites within coding regions, exhibiting high editing efficiency (> 70%). The turnover rate of Caryophyllales mitogenomes was found to be, on average, 6.1 times faster than that of plastomes. In contrast, the nucleotide substitution rate in protein-coding genes was significantly higher in plastomes than in mitogenomes. Moreover, nonsilent nucleotide substitutions in genes encoding components of the electron transfer chain were more constrained compared to those in ribosomal protein-coding genes in both plastidial and mitochondrial genomes of Caryophyllales. Together, these findings provide vital genetic resources that enhance our understanding of the dynamic evolution and phylogenetic relationships within Bougainvillea and the broader Caryophyllales order.